Agricultural research: strengthening the contribution of universities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
international workshop held in November 1997 at the IITA (International Institute for Tropical Agriculture) station at Calavi in Benin